Brachiopoda of Greece: an annotated checklist - Gerovasileiou, Vasilis (Biodivers Data J, 2016)
Abstract. BACKGROUND: Until today, only scattered species records of Brachiopoda from Greece have been included in publications on the Mediterranean brachiopod fauna. These records were mostly based on material collected during marine expeditions in the eastern Mediterranean decades ago, while few recent additional records appear in ecological studies. The aim of this paper was to give the first checklist of brachiopod species of Greece, in the framework of the Greek Taxon Information System (GTIS) initiative of the LifeWatchGreece Research Infrastructure (ESFRI), by reviewing the existing literature. NEW INFORMATION: Twelve brachiopod species have been found in Greek waters so far. The nomenclature, distribution, fossil records, ecology, and literature sources are discussed for each species.